Spiritual Grammar: Genre and the Saintly Subject in Islam and Christianity - Longo, F. Dominic (Comparative Theology: Thinking Across Traditions Ser, 2017)
Literary analysis and theological interpretation of Catholic, University of Paris chancellor Jean Gerson's (d. 1429) Donatus moralizatus and Muslim, Sufi scholar ʿAbd al-Karīm al-Qushayrī's (d. 1072) Naḥw al-qulūb. Argues that the genre of these two religious texts aims to engender saintly readers and uses grammar as metaphor for spiritual realities